2016
DOI: 10.1002/psb.1480
|View full text |Cite
|
Sign up to set email alerts
|

Topical antibacterial and antiviral agents: prescribing and resistance

Abstract: This article describes the current prescribing patterns for topical antibacterial and antiviral preparations in primary care and the factors to consider when choosing a treatment, including the evidence for antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Chaplin conducted a study about the current prescribing patterns for topical antiviral and antibacterial preparations in primary care in 2015 in England and reported that regarding the use of antivirals for skin infections, 98.64% of the prescriptions contained acyclovir and only 1.36% contained penciclovir [17]. He also reported that regarding the use of antivirals for eye infections, 40.62% of the prescriptions contained acyclovir and 59.38% contained ganciclovir [17].…”
Section: Resultsmentioning
confidence: 99%
“…Chaplin conducted a study about the current prescribing patterns for topical antiviral and antibacterial preparations in primary care in 2015 in England and reported that regarding the use of antivirals for skin infections, 98.64% of the prescriptions contained acyclovir and only 1.36% contained penciclovir [17]. He also reported that regarding the use of antivirals for eye infections, 40.62% of the prescriptions contained acyclovir and 59.38% contained ganciclovir [17].…”
Section: Resultsmentioning
confidence: 99%
“…This is in direct contrast to antibiotics administrated systemically, whose concentration at the site of infection is significantly less than that administered. Further, while topical antibiotics are usually not recommended because of the risk of resistance development [ 16 ], topical phage therapy can be desirable. As such, infection which previously required systemic antibiotic therapy such as skin, soft tissue and surgical site infection can be potentially treated with topical phage therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial eye drops serve an important role in the ophthalmic setting and have seen widespread use in both prophylaxis and treatment of bacterial ocular surface infections such as conjunctivitis and keratitis. Various antibacterial agents including chloramphenicol, ciprofloxacin and fusidic acid can be prepared as ophthalmic formulations and administered to the eye in a safe and effective manner, although the cost of these formulations restricts their widespread availability …”
mentioning
confidence: 99%